2023
DOI: 10.3390/app13021127
|View full text |Cite
|
Sign up to set email alerts
|

Independent or Combinational Application of Sheep Manure and Litter from Indigenous Field Vegetation of Quercus sp. Influences Nutrient Uptake, Photosynthesis, Intrinsic Water Use Efficiency, and Foliar Sugar Concentrations in Olive Plants (Olea europaea L., cv. “Koroneiki”)

Abstract: The recent energy crisis has increased the cost of fertilization for olive growers. This is why alternative nutrient sources, such as manures and other organic materials, could be used to sustain olive production within the framework of sustainable agriculture, by decreasing chemical fertilization inputs. A greenhouse pot experiment was established with a marl soil substrate that was modified with three amendments (sheep manure, or SM; litter from evergreen broadleaf species, or EBLS, such as Quercus sp.; thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…From the results of Table (5), it is noted that the addition of animal (O1) and vegetable (O2) organic fertilizers gave an average ounce content of chlorophyll amounted to (1.78 and 1.56) gm L -1 respectively, it is clear from the table that O1 was significantly superior to O2 with a percentage increase of (14.10) %, this is consistent with [25] who found that adding sheep manure at a rate of 30 tons hectare-1 gave the highest chlorophyll content compared to compost. Sheep manure also outperforms compost in intrinsic water use efficiency (WUEI) which provides information about the efficiency of plant water use in terms of carbon dioxide uptake and low transpiration losses, which is defined as the ratio between the rate of photosynthesis and stomatal drainage [26] and this is consistent with [27] who found that sheep manure affected WUEI in olive plants. When studying the effect of the levels of binary fertilization on the content of leaves of chlorophyll, the results showed that there were significant differences, as the level of dual fertilization (M2), which gave a value of (1.99) gm L -1 , exceeded the level of the first and second fertilization (M0 and M1), which amounted to Their values are (1.24 and 1.77) gm L -1 respectively, this is due to the fact that the addition of nitrogen with phosphorus together in a band form increases the efficiency of phosphate fertilizers, which reflects positively on the characteristics of the plant [28].…”
Section: Leaves Content Of Chlorophyll (Gm L -1 )supporting
confidence: 72%
“…From the results of Table (5), it is noted that the addition of animal (O1) and vegetable (O2) organic fertilizers gave an average ounce content of chlorophyll amounted to (1.78 and 1.56) gm L -1 respectively, it is clear from the table that O1 was significantly superior to O2 with a percentage increase of (14.10) %, this is consistent with [25] who found that adding sheep manure at a rate of 30 tons hectare-1 gave the highest chlorophyll content compared to compost. Sheep manure also outperforms compost in intrinsic water use efficiency (WUEI) which provides information about the efficiency of plant water use in terms of carbon dioxide uptake and low transpiration losses, which is defined as the ratio between the rate of photosynthesis and stomatal drainage [26] and this is consistent with [27] who found that sheep manure affected WUEI in olive plants. When studying the effect of the levels of binary fertilization on the content of leaves of chlorophyll, the results showed that there were significant differences, as the level of dual fertilization (M2), which gave a value of (1.99) gm L -1 , exceeded the level of the first and second fertilization (M0 and M1), which amounted to Their values are (1.24 and 1.77) gm L -1 respectively, this is due to the fact that the addition of nitrogen with phosphorus together in a band form increases the efficiency of phosphate fertilizers, which reflects positively on the characteristics of the plant [28].…”
Section: Leaves Content Of Chlorophyll (Gm L -1 )supporting
confidence: 72%
“…It has a great ability to chelate other elements despite its small molecular weight. It has a great ability to penetrate cell membrane, and it is highly soluble in acidic and alkaline media [16]. Its color is light yellow to brown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the authors state that more research is needed. (b) To assess the suitability of alternative nutrient sources/substrates for potted olives [15].…”
mentioning
confidence: 99%